2008
DOI: 10.1002/icd.583
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity and regulation: the impact of Mary Rothbart on the study of temperament

Abstract: Through her theoretical and empirical work, Mary Rothbart has had a profound impact on the scientific understanding of infant and child temperament. This special issue honors her contributions through the presentations of original, contemporary studies relevant to three primary themes in Rothbart's conceptual approach: the expansive scope and empirically‐derived structure of temperament, the importance of considering developmental change, and the interplay of reactive and regulatory processes. In addition to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 36 publications
0
31
0
1
Order By: Relevance
“…Due to the ease of administration and scoring, large-scale studies have typically relied exclusively on parent report questionnaires to measure temperament (Henrichs et al, 2009; Kaplan et al, 2014; Sanson, Prior, Garino, Oberklaid, & Sewell, 1987; Wessman et al, 2012). Studies involving parent reported inventories of temperament have provided empirical support for sub-dividing the construct of temperament into two broad domains—reactivity and regulation (Putnam & Stifter, 2008). Whereas reactivity has been defined as “the speed, strength, and valence [positive or negative] of an individual’s characteristic response to stimulation”, regulation has been defined as “behaviors the individual uses to control their behavioral and emotional reactions to sources of both positive and negative stimulation” (Henderson & Wachs, 2007; p. 400).…”
Section: 0 the Epidemiology Of Observed Temperament: Factor Structumentioning
confidence: 99%
“…Due to the ease of administration and scoring, large-scale studies have typically relied exclusively on parent report questionnaires to measure temperament (Henrichs et al, 2009; Kaplan et al, 2014; Sanson, Prior, Garino, Oberklaid, & Sewell, 1987; Wessman et al, 2012). Studies involving parent reported inventories of temperament have provided empirical support for sub-dividing the construct of temperament into two broad domains—reactivity and regulation (Putnam & Stifter, 2008). Whereas reactivity has been defined as “the speed, strength, and valence [positive or negative] of an individual’s characteristic response to stimulation”, regulation has been defined as “behaviors the individual uses to control their behavioral and emotional reactions to sources of both positive and negative stimulation” (Henderson & Wachs, 2007; p. 400).…”
Section: 0 the Epidemiology Of Observed Temperament: Factor Structumentioning
confidence: 99%
“…Rothbart’s approach to temperament is inclusive of a wider variety of influences than those of other temperament theorists, who focus primarily on behavioral tendencies, as opposed to including neural and physiological factors as well. Her integrated approach also allows for a more dynamic concept of temperament, with models that capture early‐appearing traits, but allow enough flexibility to recognize developmental change over time (Putnam & Stifter, 2008). This conceptualization, as articulated by Rothbart and Derryberry (1981), provided the basis for a battery of tests to measure temperament across all ages, including those employed in the current investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The model of infants' fundamental adaptive response system matches well with Rothbart and Bates's (2006) concepts and extensive research on children's temperament (Putnam & Stifter, 2008). In Rothbart and Bates's view, temperament may be traced back to constitutional variability in infants in two major components of behavioral responsivity: reactivity and self-regulation.…”
Section: Individual Variation Of Infants' Intrinsic Regulatory Functimentioning
confidence: 89%